HBx mutant-regulated RPL13AP25 mediates suboptimal virological response to entecavir and HCC progression - Yang-Hsiang Lin; Ming-Wei Lai; Yu-De Chu; Kwang-Huei Lin; Chao-Wei Hsu; Rong-Nan Chien; Po-Heng Chuang; Chih-Lang Lin; Chau-Ting Yeh (Cancer Cell International)
Abstract Background A number of effective antiviral agents for chronic hepatitis B are available worldwide, and these agents have exhibited satisfactory virologic suppression, but suboptimal responses still occur in some patients. We aimed to explore the contribution of long non-coding RNAs (lncRNAs) in mediating suboptimal responses in chronic hepatitis B patients, which remains to be fully elucidated. Methods Cox regression models were used to analyze associations between suboptimal response and clinical factors. Hepatitis B virus X (HBx) gene was sequenced from entecavir-treated patients who developed hepatocellular carcinoma (HCC). Functional assays were conducted using Transwell assays, MTT assays, and xenograft model. Results Suboptimal response was found to be a significant independent predictor of HCC development. Five of the six patients who developed HCC in the suboptimal response period were found to have HBx mutations (HBx-L100 insertion, HBx-G32R/K130M, HBx-Q87G/k130M/C143R, HBx-L123S, and HBx-H94Y/K130M). Overexpression of the HBx-H94Y/K130M mutation in HepG2.2.15 cells showed significantly increased cccDNA accumulation and enhanced cell migration compared to controls and other HBx mutants. RNA-seq analysis identified RPL13AP25 as a direct target of HBx-H94Y/K130M. RPL13AP25 was highly expressed in HCC tissues, and its elevated expression was associated with poor overall survival and enhanced cell motility and cccDNA accumulation both in vitro and in vivo. Mechanistically, both HBx-H94Y/K130M and RPL13AP25 enhanced the hyperphosphorylation of eIF4EBP1, leading to its dissociation from eIF4E, which subsequently enhances protein synthesis and ultimately contributes to HCC. Conclusions The HBx-H94Y/K130M mutant, selected during the period of suboptimal virological response, appears to promote cccDNA accumulation, likely through the upregulation of RPL13AP25, which contributed to HCC progression.